L’anarchiste et la philosophe : Antonio Atarés et Simone Weil (1941-1951) - Bernard Sicot (Cahiers de Civilisation Espagnole Contemporaine)
The correspondence between Simone Weil and Antonio Atarés in 1941 and 1942 has resulted in a striking imbalance. Whereas we are amply informed about the spiritual and philosophical preoccupations of the French philosopher during the period and have access to her letters, of the Spanish anarchist peasant who was interned in the camps of Vichy, we know nothing, and his letters are lost. The present article is an attempt to retrace the itinerary of Atarés and to restore him his voice.